Культура мовлення як необхідний чинник сучасної комунікації - Фукс, М. А. (ХНУРЕ, 2019)
A person is a part of socialization and, first of all, a person becomes himself due to communication. Socialization has vital importance for both individual's development and identify future position in society. Unreservedly, most people want to be successful, renowned, wealthy or simply have highpaying job. All these require a lot of diligence and to be able to support discussion. That is called a culture of communication. Each person starts to educate that from the moment of birth. Teachers in school have great influence on development of this competence.